PENGARUH AKSESIBILITAS JALAN DAN FASILITAS TERHADAP KEPUASAN PENGUNJUNG DI DESTINASTI WISATA KAMPOENG CIHERANG TANJUNGSARI KABUPATEN SUMEDANG - Shyfa Sri Pratama (PT. Hasba Edukasi Mandiri, 2025)
The importance of the role of road accessibility and facilities in supporting visitor satisfaction at Tourist Destinations. One of the developing Tourist Destinations in Sumedang Regency is Kampoeng Ciherang which still faces obstacles related to road quality and completeness of facilities. The purpose of this study is to determine the effect of road accessibility and facilities on visitor satisfaction, both partially and simultaneously. The research method used is quantitative with a questionnaire approach. Data were obtained using a nonprobability sampling technique with a total population of 1,223 respondents using the Slovin formula, a total of 92 respondents were obtained from the population and then analyzed descriptively, as well as verification analysis through t-test, F-test, and multiple linear regression using the SPSS version 25 application. The results of the study indicate that partially and simultaneously both road accessibility and facility variables have a significant positive effect on visitor satisfaction.